Application of Sub-Miniature Fission Chamber Neutron Detector for Neutron Flux Measurement at the RSG-GAS Reactor: Foil Activation Benchmarking - Gusman, R.; Agung, A.; Subekti, R. M.; Iswahyudi, F. N.; Susanti, F.; Pinem, S. (Atom Indonesia, 2026)
Accurate neutron flux measurement is essential for reactor characterization and utilization. At the RSG-GAS reactor, previous flux measurements relied on the foil activation method. While this method provides high accuracy, it lacks real-time capability due to its requirement for irradiation, post-irradiation cooling, and subsequent gamma spectroscopy for activity assessment. Direct online measurements of thermal neutron flux in the RSG-GAS reactor irradiation positions were performed using a Sub-Miniature Fission Chamber (SMFC) detector, where the flux was determined from the detector's output current proportional to fission events. This approach offers a viable alternative to the conventional foil activation technique by eliminating its time-consuming process and multiple uncertainty sources. After applying a correction factor obtained from gold foil activation reference measurements and the combined measurement uncertainty was quantified as ± 4.0%, results showed an axial flux distribution peaking at 200 mm height from the bottom of the core with maximum values of 4.997 x 1012 ± 0.199 x 1012 n/cm².s at central iradiation position (CIP E7), 6.212 x 1012 ± 0.248 x 1012 n/cm².s at iradiation position (IP B6), and 2.096 x 1012 ± 0.083x1012 n/cm².s at reflector element with plug (BS+ A2) under 200 kW operation. Radial mapping at 600 mm height from the bottom of the core revealed a maximum flux of 1.230 x 1012 ± 0.049 x 1012 n/cm².s at IP (G7). These results demonstrate that the Sub-Miniature Fission Chamber (SMFC) enables real-time neutron flux monitoring and provides a viable alternative to the conventional foil activation technique.